Nurses' experience of occupational alienation in the clinical setting: A content analysis - Maryam Salehian; Hamideh Goli; Hamideh Yazdimoghaddam (Wolters Kluwer Medknow Publications, 2023)
Background: Job alienation of nurses leads to adverse consequences such as occupational dysfunction and low quality of health-care services provided by these individuals to patients. This study aimed to explain nurses' experience of occupational alienation in the clinical setting. Materials and Methods: This qualitative study was conducted using the content analysis method. Data were collected via 18 in-depth and semistructured interviews from nurses working in the hospitals in Sabzevar, Iran. The participants were selected via purposive sampling and continued till data saturation. The obtained data were simultaneously analyzed using conventional qualitative content analysis. Results: The qualitative analysis of data content led to the extraction of the themes that reflected the nurses' experience of occupational alienation in the clinical environment. After the transcription of each interview, the obtained data were broken down into codes in the form of sentences and paragraphs related to the main concept. The codes were reviewed several times and the relevant semantic unit codes were written down and classified based on conceptual and semantic similarity. Qualitative data analysis led to the emergence of 260 initial codes, 120 subcategories, 30 main categories, and 6 themes. Finally, the main theme of the "nursing gradual separation from caring and clinical aspect" was extracted. Conclusions: According to the results, occupational alienation reduces the quality of patient care, weakens nurses, and reduces the continuity of their effective and active presence in the provision of care services and clinical decision-making. Therefore, managerial and organizational interventions are required to address this issue.